Seasonal and spatial variability of Phytoplankton primary production in a shallow temperate Coastal Lagoon (Ria Formosa, Portugal) - B. Domingues, Rita (2022)
Coastal lagoons are among the most productive ecosystems in the world, and they provide a wide range of ecosystem services and resources. In the Ria Formosa (southern Portugal), phytoplankton production has rarely been addressed. The main goal of this study is thus to evaluate the variability of phytoplankton production and photosynthetic characteristics over the seasonal cycle and in different locations (landward, urban, intermediate, and seaward boundaries) of the Ria Formosa coastal lagoon, subjected to distinct natural and anthropogenic stressors. Primary production was evaluated using the 14C incorporation technique, and photosynthetic parameters were estimated by fitting photosynthesis-irradiance curves. Primary production showed significant seasonal variations, with higher values in the summer associated with lower euphotic depths, higher water temperatures, and higher nutrient concentrations. No spatial differences were found for primary production or photosynthetic parameters. Primary production values were lower than previous estimates, which reflects an improvement in water quality in the Ria Formosa, but values are higher than primary production estimates for other temperate coastal ecosystems, which reflects the highly productive nature of this coastal lagoon.